Distribuição espacial da cobertura vacinal contra o papilomavírus humano- HPV no estado do Maranhão - FERNANDES , Renata Pinheiro Pedra (2024)
Introduction: Human Papillomavirus (HPV) infection is common worldwide, primarily transmitted through sexual contact. It is estimated that 80% of sexually active individuals will be infected with the virus at some point in their lives. Vaccination remains the best and most effective form of prevention. Understanding vaccination coverage and analyzing its spatial distribution can strengthen disease surveillance and monitoring actions and their implications. Objective: To describe the spatial distribution of HPV vaccination coverage among boys and girls in the state of Maranhão. Methods: This is a retrospective and ecological study on HPV vaccination coverage in the state of Maranhão, with the 19 health regions and 217 municipalities as the units of analysis. The study population includes all boys and girls immunized against HPV residing in the state of Maranhão. Information on doses administered by age and sex was collected from the National Immunization Program (NIP), and the target population from the 2010 Census of the Brazilian Institute of Geography and Statistics (IBGE). The construction of age cohorts followed the methodology recommended by the NIP, identifying groups of eligible girls and boys for vaccination in different age ranges. For girls, cohorts were defined with ages 13, 14, and 15 in 2021, while for boys, cohorts covered ages 16, 17, and 18 in the same year. To calculate vaccination coverage, the approach adopted was the cumulative coverage per cohort recommended by the NIP. The completeness of vaccination coverage was calculated using the number of doses administered in the specified population. Categorization of the cumulative vaccination coverage rate by municipality as inadequate (<80%) and adequate (≥80%) followed NIP guidelines and was performed separately for the first and second doses. Data spatialization was performed using QGIS software, version 3.22. Results: It was observed that 16 (84.2%) of the 19 health regions in Maranhão achieved adequate vaccination coverage (≥80%) for the first dose of cohort 1 girls, and 5 (26.3%) achieved adequate coverage for the second dose. For cohorts 2 and 3 of girls, both the first and second doses had coverage rates lower than recommended in all nineteen health regions of the state. Regarding HPV vaccination coverage for boys, only the health regions of Açailândia (82.6%), Imperatriz (92.7%), Pedreiras (93.6%), Santa Inês (91.5%), and São João dos Patos (85%) achieved adequate coverage in cohort 1, for the 1st dose. In the remaining cohorts, coverage was inadequate regardless of the dose administered. Vaccination coverage in girls reveals that, for the 1st dose, 60% of the 217 municipalities achieved adequate coverage in Cohort 1, contrasting with only 1% in Cohort 2 and 0.5% in Cohort 3. For the 2nd dose, 32% of municipalities in Cohort 1 reached the target, while only 5% in Cohort 2 were successful, and no municipality in Cohort 3 achieved adequate coverage. Vaccination in boys shows that, for the 1st dose, 38% of municipalities in Cohort 1 achieved adequate coverage, 12% in Cohort 2, and none in Cohort 3. As for the 2nd dose, only 1% of municipalities in Cohort 2 achieved adequate coverage. Conclusion: The analysis of HPV vaccination coverage in Maranhão reveals challenges in the implementation of the immunization program, especially in spatial distribution. The analysis reveals that, when categorizing coverage by health regions, only the first dose of cohort 1 reached the target for both boys and girls. The second dose, however, achieved adequate coverage only for girls in cohort 1. The variation between doses and cohorts indicates the need to improve promotion and awareness strategies, adapting them to each region and municipality. Municipal analysis highlights a significant decline in coverage between doses, indicating challenges in subsequent phases of vaccination. Targeted measures, such as educational campaigns and regional adaptation, are crucial to optimize vaccination coverage in the state.